The predictive content of sectoral stock prices: a US-euro area comparison - Magnus Andersson; Antonello D'Agostino; Gabe de Bondt; Moreno Roma (European Central Bank (ECB), 2011)
This paper examines the out-of-sample forecast performance of sectoral stock market indicators for real GDP, private consumption and investment growth up to 4 quarters ahead in the US and the euro area. Our findings are that the predictive content of sectoral stock market indicators: i) is potentially strong, particularly for the financial sector, and is stronger than that of financial spreads; ii) varies over time, with a substantial improvement after 1999 for the euro area; iii) is stronger for investment than for private consumption; and iv) is stronger in the euro area than in the United States.
Keywords: C53; E37; G12; 330; consumption and investment; euro area; forecasting real GDP; sectoral stock prices; stock market valuation metrics; US